Socially Assigned Gender Nonconformity and School Violence Experience Among Transgender and Cisgender Adolescents - Klemmer, Cary L. (Journal of interpersonal violence, 2021)
Although literature documents the experiences of socially assigned gender nonconformity (SAGNC) by minority sexual orientation (i.e., lesbian, gay, and bisexual [LGB]), examination of the role of gender expression on school violence outcomes in the presence of sexual orientation and gender identity is not well understood. This study describes SAGNC among a representative sample of adolescents, accounting for sexual orientation and gender identity (e.g., transgender). A secondary data analysis was conducted using Youth Risk Behavior Survey data from Los Angeles Unified School District high schools in 2013 (N = 1,496). The prevalence of school violence by self-reported SAGNC and gender identity was obtained. Associations between SAGNC and school violence were examined using multivariate logistic regression adjusted for mischievous response bias. Two hundred ninety-one (19.5%) adolescents reported SAGNC. Having missed school due to a safety concern and being bullied in the past year were more common among socially assigned gender nonconforming adolescents than those who conformed to gender expression expectations. Socially assigned gender nonconforming adolescents, regardless of sexual orientation or gender identity, are at greater risk of missed school due to safety concerns, and bullying, as compared with those who conform to norms of gender expression. Future research should measure SAGNC, sexual orientation, gender identity, and expression with larger representative samples of school populations across contexts (urban and rural), and inclusive of structural factors (e.g., school climate) to guide the development of prevention efforts.